การปรับสภาพเบื้องต้นและการผลิตไวน์จากผลแก้วมังกรแดง Hylocereus polyrhizus - วิทวัส ขวัญเมือง (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
Red dragon fruit (Hylecereus polyhizus) is well known for the attractive and rich nutrient contents. The proximate analysis of red dragon fruit was detected the results showed 88.20 % moisture; 0.17 % protein; 0.40 % fat 0.12 % ash and 8.20 % fiber. The antioxidant properties of red dragon fruit revealed 74.36 % DPPH radical scarvenging and total phenolic compound 155.42 mgGAE/ml. of red dragon fruit. Wine is the product of complex interactions between microorganism. The use of Saccharomyces cerevisiae 4019, Saccharomycodes ludwigii and Hanseniaspora uvarum in in single pure, mixed and sequential mixtures has been studied to characterize red dragon fruit wine. In pure cultures, S. cerevisiae 4019 at the level of 8 x 108 cfu/ml could produce highest amount of ethanol compared to different initial concentration of inoculum. The wines obtained from using non-saccharomyces yeast at the same inoculum were evaluated compared to the saccharomyces wine before . It was found that the wine from non-saccharomyces group received more preference in odor. Mixed cultures (mixed and sequential) fermentation had been studied. It was found that the sequential cultures fermentation of Saccharomyces cerevisiae 4019 and Saccharomycodes ludwigii was combination in producing wine with 11.4 % (v/v) ethanol. Antioxidant of red dragon fruit wines was performed by DPPH scavenging and total phenolic compound content. % DPPH radical scavenging of red dragon fruit wines were gradually decreased (p ≤ 0.05) through the fermentation period except that for wine made from S. cerevisiae 4019 at the level of 4 x 108 cfu/ml.